Actinium-225-PSMA radioligand therapy of metastatic castration-resistant prostate cancer (WARMTH Act): a multicentre, retrospective study - Sathekge, Mike; Lawal, Ismaheel O; Bal, Chandrasekhar; Bruchertseifer, Frank; Ballal, Sajana; Cardaci, Giuseppe; Davis, Cindy; Eiber, Mathias; Hekimsoy, Türkay; Knoesen, Otto; Kratochwil, Clemens; Lenzo, Nat P; et al. (The lancet. Oncology, 2024)
Background - Actinium-225 (225Ac) prostate-specific membrane antigen (PSMA) radioligand therapy (RLT) is a novel therapy for metastatic castration-resistant prostate cancer (mCRPC). We aimed to report the safety and antitumour activity of 225Ac-PSMA RLT of mCRPC in a large cohort of patients treated at multiple centres across the world. - Methods - This retrospective study included patients treated at seven centres in Australia, India, Germany, and South Africa. We pooled data of consecutive patients of any age and Eastern Cooperative Oncology Group performance status with histopathologically confirmed adenocarcinoma of the prostate who were treated with one or more cycles of 8 MBq 225Ac-PSMA RLT administered intravenously for mCRPC. Previous lines of mCRPC treatment included taxane-based chemotherapy, androgen-receptor-axis inhibitors, lutetium-177 (177Lu) PSMA RLT, and radium-223 dichloride. The primary outcomes were overall survival and progression-free survival. - Findings - Between Jan 1, 2016, and May 31, 2023, 488 men with mCRPC received 1174 cycles of 225Ac-PSMA RLT (median two cycles, IQR 2-4). The mean age of the patients was 68·1 years (SD 8·8), and the median baseline prostate-specific antigen was 169·5 ng/mL (IQR 34·6-519·8). Previous lines of treatment were docetaxel in 324 (66%) patients, cabazitaxel in 103 (21%) patients, abiraterone in 191 (39%) patients, enzalutamide in 188 (39%) patients, 177Lu-PSMA RLT in 154 (32%) patients, and radium-223 dichloride in 18 (4%) patients. The median follow-up duration was 9·0 months (IQR 5·0-17·5). The median overall survival was 15·5 months (95% CI 13·4-18·3) and median progression-free survival was 7·9 months (6·8-8·9). In 347 (71%) of 488 patients, information regarding treatment-induced xerostomia was available, and 236 (68%) of the 347 patients reported xerostomia after the first cycle of 225Ac-PSMA RLT. All patients who received more than seven cycles of 225Ac-PSMA RLT reported xerostomia. Grade 3 or higher anaemia occurred in 64 (13%) of 488 patients, leukopenia in 19 (4%), thrombocytopenia in 32 (7%), and renal toxicity in 22 (5%). No serious adverse events or treatment-related deaths were recorded. - Interpretation - 225Ac-PSMA RLT shows a substantial antitumour effect in mCRPC and represents a viable therapy option in patients treated with previous lines of approved agents. Xerostomia is a common side-effect. Severe bone marrow and renal toxicity are less common adverse events. - Funding - None.
Online verfügbar: 11. Januar 2024, Artikelversion: 29. Januar 2024
Gesehen am 23.08.2024